PENGARUH REBRANDING TERHADAP LOYALITAS DENGAN CITRA MEREK SEBAGAI VARIABEL MEDIASI (STUDI PADA PO SUGENG RAHAYU) - HENDRA WINATA, DADANG; LESTARI ANDJARWATI, ANIK (Jurnal Ilmu Manajemen (JIM), 2018)
The current public transport business is becoming very competitive. The company must have a competitive strategy, one of the strategies of competing in the company was rebranding. Rebranding can provide a positive influence against the image of a brand due to rebranding strategy undertaken to continue to create a positive image of a brand. A positive brand image can be associated with brand loyalty, because loyalty is the core goal of the attempted by marketers. The purpose of this study is to analyze and discuss the influence of rebranding towards brand image with loyalty as mediation variables. Sampling technique used is non-judgemental sampling with probalbility method of sampling. The sample used as many as 220 people. The respondents in this study was the passenger PO Sugeng Rahayu with ages ranging from 18 years onwards. The scale of measurement using the likert scale. Measuring instrument used is a question form. Data analysis by using path analysis. The results showed that rebranding had a significant effect on brand image, and brand image had a significant effect on loyalty. The results of this study indicate that rebranding does not directly affect loyalty and through brand image as a mediating variable. In this mediation test rebranding and loyalty are proven to be fully mediated by brand image. Keywords: brand image; loyalty; rebranding